A Tentative Idea of Virtual Simulation Experiment of FOF Based on Blockchain. Issue 1 (March 2020) - Xu, Feng; He, Dawei; Guan, Chengtian
Abstract: With the modernization of education, National Virtual Simulation Experimental Teaching Project has become an important measure to reform the existed teaching method. This paper proposes and expounds a tentative idea of virtual simulation experiment of FOF. Firstly, it introduces this experiment's necessity, lists its core elements, and analyses its advantages and competitiveness. And then it explains experiment's principles and lists operation steps. Finally, it illustrates anticipated outcomes of the experiment and makes the summary of this experiment's advantages and prospects.